Here I am [compact disc, unabridged] : a novel - Foer, Jonathan Safran, 1977- (Macmillan Audio, 2016)
The story of a fracturing family in a moment of crisis. As Jacob and Julia and their three sons are forced to confront the distances between the lives they think they want and the lives they are living, a catastrophic earthquake sets in motion a quickly-escalating conflict in the Middle East. At stake is the very meaning of home, and the fundamental question of how much life one can bear.